K problematice tenkojehlových punkcních vysetrení prostaty - Zavadilová, H; Habanec, B; Ostrizek, D (Ceskoslovenska patologie, 1984)
The technology of fine-needle aspiration of prostatic tissue was described and its results discussed in a group of 45 patients. Demonstration of findings included: normal cytology, adenomyomatous hyperplasia with mosaic pattern of epithelial cells, acute purulent inflammation, chronic inflammation with pseudoxanthomatous lipophages , seminal vesicles with atypical non-cohesive epithelial cells, and neoplasia.
Keywords: dospělí; prostata; Prostate; Adult; prostatitida; lidé; nádory prostaty; Prostatic Neoplasms; hyperplazie prostaty; Male; jehlová biopsie; Aged; Biopsy, Needle; Prostatitis; lidé středního věku; Prostatic Hyperplasia; senioři; mužské pohlaví; Middle Aged; Humans